Low-dose cyclophosphamide-induced acute hepatotoxicity - Subramaniam, S. Ravih (International Scientific Literature, Inc., 2013)
Patient: Male, 48 Final Diagnosis: Low dose cyclophosphamide-induced acute hepatotoxicity Symptoms: Epigastric pain Medication: Withdrawal of cyclophosphamide Clinical Procedure: — Specialty: Nephrology • Hepatology • Gastroenterology • Toxicology OBJECTIVE: Unexpected drug reaction BACKGROUND: Cyclophosphamide is commonly used to treat cancers, systemic vasculitides, and kidney diseases (e.g., lupus nephritis and focal segmental glomerulosclerosis). Acute adverse effects include bone marrow suppression, hemorrhagic cystitis, nausea, vomiting, and hair loss. Hepatotoxicity with high dose cyclophosphamide is well recognized but hepatitis due to low dose cyclophosphamide has rarely been described. CASE REPORT: We report the case of a 48-year-old Chinese man with a rapidly progressive glomerulonephritis secondary to granulomatosis with polyangiitis who developed severe acute hepatic failure within 24 hours of receiving low-dose intravenous cyclophosphamide. The diagnosis of granulomatosis with polyangiitis was supported with a positive c-ANCA serology. The patient was treated with high dose methylprednisolone, plasmapheresis, intermittent hemodialysis, and low-dose intravenous cyclophosphamide. CONCLUSIONS: Hepatotoxicity may occur even after low-dose intravenous cyclophosphamide treatment. To the best of our knowledge, this is the first report of severe, non-viral, liver inflammation developing within 24 hours of administration of low-dose intravenous cyclophosphamide (200 mg). Physicians should be aware of this serious adverse reaction and should not repeat the cyclophosphamide dose when there is hepatotoxicity caused by the first dose. Initial and follow-up liver function tests should be monitored in all patients receiving cyclophosphamide treatment.